Pengaruh Model Problem Based Learning (PBL) Berbantuan Media Interaktif Berbasis Wordwall Terhadap Kemampuan Berpikir Kritis dan Pemahaman Pelajaran Matematika Siswa Kelas IV SD - Linda Eka Putri; Neza Agusdianita; Osa Juarsa (Jurnal Kajian Pendidikan Dasar, 2026)
This study examines the effect of Problem-Based Learning (PBL) model assisted by Wordwall-based interactive media on critical thinking skills and mathematical conceptual understanding of fourth-grade elementary school students. A quasi-experimental design with posttest-only control group involving 40 students at SD Negeri 112 Rejang Lebong was employed. The experimental class received PBL instruction with Wordwall integration, while the control class received conventional instruction. Data were collected through validated multiple-choice tests measuring critical thinking (10 items) and conceptual understanding (6 items), analyzed using Independent Sample T-Test and N-Gain. Results demonstrate significant effects on both variables: critical thinking (sig. 0.000 < 0.05, N-Gain 63% vs. 30%) and conceptual understanding (sig. 0.003 < 0.05, N-Gain 53% vs. -12%). The study reveals a strong reciprocal relationship between critical thinking and conceptual understanding, where both develop simultaneously through PBL's pedagogical structure. Wordwall functions as a catalyst synchronizing and amplifying the interaction between variables through immediate feedback and multiple representations. The model proves effective in transforming surface learning into deep conceptual understanding while developing 21st-century skills. This finding contributes to developing effective, contextual mathematics learning models aligned with Merdeka Curriculum demands and 21st-century learning requirements in elementary education.